Imagination of our Present: Jean Baudrillard from the The System of Objects to the Domotics and the Internet of Things - Barile, Nello (Italian Sociological Review, 2017)
The article reflects on the connections between Baudrillard’s first reflections on space, design and technology and the contemporary innovations that blurred completely the border between virtual and real. Just because not so present in the international debate on the new web as in the nineties, Jean Baudrillard’s work still deserves to be rediscovered and applied to the innovations that mark our time. Probably only authors such as Geert Lovink (2011) are using the reference to the French philosopher to establish a union trait between the old web and the so-called web 2.0. This is why it might be more useful to reflect on how the visionary character of Baudrillard has anticipated a future vision, still to be explored systematically. For this reason in the following article I will try to compare Baudrillard’s first work which is an insightful dissertation on the relationship between the virtual space of communication and the physical space of the architecture, forerunning one of the latest trends in digital innovation that is the integration between bits and atoms as in the recent debate on the end of the ‘digital dualism’ (Jurgenson, 2011).